Інтерактивні технології як засіб розвитку креативного мислення учнів на уроках англійської мови - Чапюк, Юлія; Сhapyuk, Yulia (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті розглядається питання ефективності використання інтерактивних технологій на уроках англійської мови. Розкривається актуальність і практична цінність інтерактивних технологій, особливості інтерактивного навчання. Акцентується увага на характеристиці таких технологій, як «Карусель», «Акваріум», «Мікрофон». . In the article some aspects are considered in relation to essence description of concept “creative thinking”. Attention is focused on the deep understanding of term “interactive” etymology for the concretization of researched phenomenon’s content identified its special feature from the point of view of pedagogics. The present article deals with implementation of interactive learning for English classes. Some examples of interactive techniques are provided and means of its conducting are analyzed. The necessity of creativity development in the aspect of forming a creative personality is proved that potentially important for pedagogics. The author draws a conclusion that the essence of creative thinking and interactive techniques are in the discovery and creation of something qualitatively new that has significant value.
Interactive technologies as means of development of creative thinking of pupils at the English lessons
Keywords: іноземна мова; інтерактивні технології; метод; foreign language; interactive technology; method